1999
DOI: 10.1128/aem.65.4.1564-1569.1999
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Resistance of Natural Isolates of Escherichia coli O157 to High Hydrostatic Pressure, Mild Heat, and Other Stresses

Abstract: Strains of Escherichia coli O157 isolated from patients with clinical cases of food-borne illness and other sources exhibited wide differences in resistance to high hydrostatic pressure. The most pressure-resistant strains were also more resistant to mild heat than other strains. Strain C9490, a representative pressure-resistant strain, was also more resistant to acid, oxidative, and osmotic stresses than the pressure-sensitive strain NCTC 12079. Most of these differences in resistance were observed only in st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
68
0
2

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(75 citation statements)
references
References 24 publications
(27 reference statements)
5
68
0
2
Order By: Relevance
“…Recent years have seen significant research on the inactivation of microorganisms in foods by HP (Dogan & Erkmen, 2004;Smiddy et al, 2004Smiddy et al, , 2005Donaghy et al, 2007). Different microorganisms react with different degrees of resistance to HPP treatment, and indeed there can be vast HPP sensitivity among bacterial species and even strains (Alpas et al, 1999;Benito et al, 1999;Pagán & Mackey, 2000). Alpas et al (1999) reported viability losses of between 0.5 and 8.5 logs among pathogenic bacterial strains.…”
Section: Effect Of Hpp On Microbial Food Safetymentioning
confidence: 99%
“…Recent years have seen significant research on the inactivation of microorganisms in foods by HP (Dogan & Erkmen, 2004;Smiddy et al, 2004Smiddy et al, , 2005Donaghy et al, 2007). Different microorganisms react with different degrees of resistance to HPP treatment, and indeed there can be vast HPP sensitivity among bacterial species and even strains (Alpas et al, 1999;Benito et al, 1999;Pagán & Mackey, 2000). Alpas et al (1999) reported viability losses of between 0.5 and 8.5 logs among pathogenic bacterial strains.…”
Section: Effect Of Hpp On Microbial Food Safetymentioning
confidence: 99%
“…This latter is especially important as care has to be taken to choose the appropriate target strains for testing the efficacy of novel processes, i.e. the most resistant strains, and when possible, multiple stress resistant strains (Benito et al 1999;Sherry et al 2004). A number of studies have reported that the resistance of a given species to a preservation technology may greatly vary amongst strains.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported that the resistance of a given species to a preservation technology may greatly vary amongst strains. Intraspecies resistance variation has been reported for several food preservation technologies (Patterson et al 1995;Alpas et al 1999;Benito et al 1999;Mañas et al 2000;Lado and Yousef 2003;Á lvarez et al 2003;Sherry et al 2004). Results published by Alpas et al (1999) showed that intraspecies variation in resistance to high hydrostatic pressure was remarkably wider for Staphylococcus aureus than for other micro-organisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of microbial cells to UHHP depends on factors such as magnitude of pressure, pressurization time, temperature, initial number of cells, types of microbial cells, suspending media, and presence of antimicrobial substances (Mackey et al, 1995;Patterson et al, 1995;Benito et al, 1999;Alpas et al, 2000;Ritz et al, 2000;Furukawa et al, 2002). In view of the limited available information on the pressure resistance of foodborne pathogens (Metrick et al, 1989;Isaacs & Chilton, 1995;Patterson et al, 1995;Alpas et al, 1999Alpas et al, , 2000Benito et al, 1999), the current study was undertaken to determine the interactions between hydrostatic pressure, pressurization time, composition of media and cell age during pressurization on Listeria monocytogenes.…”
Section: Introductionmentioning
confidence: 99%